Rights by Fortune or Fight? Reexamining the Addition of Sex to Title VII of the Civil Rights Act. Issue 2 (28th November 2018) - Krimmel, Katherine
Abstract : It is widely believed that the extension of protection against employment discrimination to women through Title VII of the Civil Rights Act (CRA) was a fluke, the product of an attempted "killer amendment" by civil rights opponents gone awry. My analysis challenges this conventional wisdom, showing that the coalition of Republicans and southern Democrats in support of the sex amendment to Title VII was consistent with broader patterns of support for the Equal Rights Amendment (ERA) in the early to mid‐20th century. In other words, support appears to have been sincere, not sophisticated—proponents preferred a CRA with the sex amendment to one without. I proceed to show that concern about the direct impact on women, and not simply the instrumental impact on labor, played an important role in motivating this support. But, I also find reason for caution in interpreting support for workplace rights as evidence of broad support for women's rights at this time.